First record of vancomycin-resistant Enterococcus faecium in Canadian wildlife - Oravcova, Veronika; Janecko, Nicol; Ansorge, Antonin; Masarikova, Martina; Literak, Ivan (Environmental microbiology reports, 2014)
In this study, we focused on spreading of vancomycin-resistant enterococci (VRE) to the environment. We studied that weather crows in Canada may be carriers and potentially reservoirs of VRE with vanA gene. We have found one multi-resistant isolate of Enterococcus faecium sequence type (ST) 448 with vanA gene on Prince Edward Island. This study is the first report of VRE in Canadian wildlife.
Keywords: zvířata; Animals; Gram-Positive Bacterial Infections; rezistence na vankomycin; Animal Diseases; Canada; grampozitivní bakteriální infekce; nemoci zvířat; divoká zvířata; Enterococcus faecium; Animals, Wild; Vancomycin Resistance; Kanada